PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR IPS DI KELAS V - ASRI, BONI; Harni, Harni; S, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research to knowing the effect of Cooperative Learning Model Jigsaw Type of learning outcomes in Social Science in Class V SDN 10 2X11 Kayutanam Padang Pariaman Regency. This research based on quantitative research with experimental research method, and quasy experimental research design. The population in this research is 145 people with amount sample is 32 people, which data collected  using purposive sampling. Instrument that used to collecting data in this research is objective test with multiple choices. The result of this research is tcount> ttable, 3,46 > 2,04 with α = 0,05 it means Ha is accepted. The average posttest result in experiment class is 87,75 and control class is 76,75. As Ha is accepted, means Cooperative Learning Type Jigsaw have affected on student learning outcomes in Social Science in Class V SDN 10 2X11 Kayutanam Padang Pariaman Regency. Keyword: Cooperatif Learning Jigsaw Type; Learning Outcomes; Social Science